Gene expression profiles of circulating tumor cells versus primary tumors in metastatic breast cancer. Issue 1 (28th June 2015) - Onstenk, Wendy; Sieuwerts, Anieta M.; Weekhout, Marleen; Mostert, Bianca; Reijm, Esther A.; van Deurzen, Carolien H.M.; Bolt-de Vries, Joan B.; Peeters, Dieter J.; Hamberg, Paul; Seynaeve, Caroline; Jager, Agnes; de Jongh, Felix E.; et al.
Highlights In 62 metastatic breast cancer (MBC) patients with ≥5 CTCs starting first-line treatment. Expression levels of 35 CTC-specific genes were compared with primary tumors. In 48% we observed large discordance between primary tumor and CTCs. In 24% expression of the estrogen receptor was discordant. Discordance in ER had prognostic significance, whereas overall discordance had not.